Why should early-career scientists publish in society journals - Stephen K. Dolan; Lori D. Banks; Wenqi Yu (mBio, 2024)
ABSTRACTIn this editorial, written by early-career scientists, we advocate for the invaluable role of society journals in our scientific community. By choosing to support these journals as authors, peer reviewers, and as editors, we can reinforce our academic growth and benefit from their re-investment back into the scientific ecosystem. Considering the numerous clear merits of this system for future generations of microbiologists and more broadly, society, we argue that early-career researchers should publish our high-quality research in society journals to shape the future of science and scientific publishing landscape.